Pengaruh Penyuluhan dengan Metode Ceramah dan Media Audio Visual terhadap Pencegahan Tuberkulosis di Puskesmas Alalak Tengah Kota Banjarmasin - Aulia Resti Anggraeni; Hiryadi Hiryadi; Anita Agustina (PPNI UNIMMAN, 2025)
Tuberculosis (TB) is an infectious disease that remains a public health problem in Indonesia, including in Banjarmasin City. Low public knowledge and awareness of clean and healthy living behaviors (PHBS) are also factors in the high rate of TB transmission. Health education is a strategic step in addressing this problem. This study aims to determine the effect of health education using lecture methods and audio-visual media on increasing knowledge in TB prevention efforts in the Alalak Tengah Community Health Center working area. The research design used was a pre-experimental study with a one-group pre-test post-test design approach. The study sample consisted of 51 respondents selected by purposive sampling. The research instrument was a questionnaire administered before and after the education, then analyzed using the Wilcoxon test. The results showed a significant increase in knowledge after the education intervention (p value <0.05). Before the education, most respondents were in the sufficient and poor knowledge categories, while after the education, most respondents moved to the good knowledge category. This indicates that the combination of lecture methods and audio-visual media can effectively increase public understanding. Delivering information through visualization has proven to be more engaging and easier to understand for a wide range of audiences. The conclusion of this study is that this outreach method is effective as a medium for educating the public about TB prevention. A similar approach can be implemented more widely in other regions to support the national TB control program. Consistent and sustainable education programs are essential to maintain high levels of public knowledge. The involvement of health workers, cadres, and community leaders is also a crucial factor in the success of outreach. This strategy is expected to be replicated in other regions with a high TB ​​burden.